Adjustment and Growth in Sub-Saharan Africa - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 1999)
This paper analyzes the factors affecting economic growth in sub-Saharan Africa, using data for 1981-97. The results indicate that per capita real GDP growth is positively influenced by economic policies that raise the ratio of private investment to GDP, promote human capital development, lower the ratio of the budget deficit to GDP, safeguard external competitiveness, and stimulate export volume growth. The favorable evolution of these variables played an important role in the region's apparent postreform recovery of 1995-97. The paper also discusses a policy framework to promote sustainable economic growth and reduce poverty in sub-Saharan Africa.